A review of library e-service quality scales - Mohd Zain, Wahidah; Othman, Roslina (Universiti Teknologi MARA Cawangan Johor & Persatuan Pustakawan Malaysia, 2014)
There has been a growing importance of e-service over the past 10 years, and libraries are continuously updating their capability to offer users with the enhanced and easy access of the service. It is necessary to carry out some form of assessment to justify the reality of the situation, whether the current libraries offer quality e-service and satisfy their users or not. The purpose of this paper was to review the existing models developed in accessing the quality of library e-service. Literature search method will be used to identify the most comprehensive model that can be implemented in evaluating the quality of library e-service. Since prominent models of service quality and the quality of e-service in non-library setting have been used as the basis for the development of the models for the library setting, only selected prominent models and their limitations will be highlighted. From the review, it was found that the hierarchical type of model is the most comprehensive model in service quality, e-service quality for non-library setting, as well as for the library setting. This paper also suggests that libraries should adopt models that have been developed originally from the library setting, as different types of users have different set of expectations and needs. Limited research have addressed on the issues of library e-service quality models and assessments. Therefore, the findings should be valuable to academics and also practitioners.